Myocardial fibrosis and arrhythmic burden in systemic sclerosis. (8th February 2022) - Ross, Laura; Costello, Benedict; Brown, Zoe; Hansen, Dylan; Lindqvist, Anniina; Stevens, Wendy; Burns, Andrew; Prior, David; Nikpour, Mandana; La Gerche, André
Abstract: Objectives: Cardiac complications of SSc are a leading cause of SSc-associated death. Cardiac imaging for identifying substrate abnormality may be useful in predicting risk of cardiac arrhythmias or future cardiac failure. The aim of this study was to quantify the burden of asymptomatic fibro-inflammatory myocardial disease using cardiac magnetic resonance imaging (CMR) and assess the relationship between asymptomatic myocardial fibrosis and cardiac arrhythmias in SSc. Methods: Thirty-two patients with SSc with no documented history of pulmonary vascular or heart disease underwent CMR with gadolinium and 24-h ambulatory ECG. Focal myocardial fibrosis was assessed using post-gadolinium imaging and diffuse fibro-inflammatory myocardial disease quantified using T1- and T2-mapping. CMR results were compared with an age- and sex-matched control group. Results: Post-gadolinium focal fibrosis was prevalent in SSc but not controls (30% vs 0%, p < 0.01).. T1-mapping values (as a marker of diffuse fibrosis) were greater in SSc than controls [saturated recovery single-shot acquisition (SASHA): 1584 ms vs 1515 ms, P < 0.001; shortened Modified look locker sequence (ShMOLLI): 1218 ms vs 1138 ms, p < 0.001]. More than one-fifth (22.6%) of the participants had ventricular arrhythmias on ambulatory ECG, but no associations between focal or diffuse myocardial fibrosis and arrhythmias were evident. Conclusion: In SSc patients without evidence of overt cardiac disease, a high burden of myocardial fibrosis and arrhythmias was identified. However, there was no clear association between focal or diffuse myocardial fibrosis and arrhythmias, suggesting CMR may have limited use as a screening tool to identify SSc patients at risk of future significant arrhythmias. Graphical Abstract: